AIAA Scitech 2021 Forum 2021
DOI: 10.2514/6.2021-0854
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of interaction between stationary crossflow instabilities and forward-facing steps

Abstract: We study the interaction between a stationary crossflow instability and forward-facing steps in a swept-wing boundary layer using Direct Numerical Simulations (DNS). The stationary primary crossflow mode is imposed at the inflow. Steps of several heights are modeled. Particular emphasis is placed on ensuring a fully stationary solution, in order to isolate the modulation of the primary instability at the step and the generation of stationary secondary perturbations. The main features of the base flow are step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…This behaviour is in agreement with previous experimental observations by Eppink (2020b) and Rius-Vidales & Kotsonis (2021). In addition, the numerical results of Casacuberta et al (2021) identified a series of near-wall perturbation streaks downstream of the FFS edge developing at the spanwise wavelength of the stationary CF vortices. Given that the wavelength of these secondary perturbations coincides with the primary CF disturbance, they manifest as a secondary peak near the wall superimposed on the disturbance profile as shown in Tufts et al (2017) and Eppink (2020b).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…This behaviour is in agreement with previous experimental observations by Eppink (2020b) and Rius-Vidales & Kotsonis (2021). In addition, the numerical results of Casacuberta et al (2021) identified a series of near-wall perturbation streaks downstream of the FFS edge developing at the spanwise wavelength of the stationary CF vortices. Given that the wavelength of these secondary perturbations coincides with the primary CF disturbance, they manifest as a secondary peak near the wall superimposed on the disturbance profile as shown in Tufts et al (2017) and Eppink (2020b).…”
Section: Introductionsupporting
confidence: 91%
“…Nonetheless, recent numerical (e.g. Tufts et al 2017;Cooke et al 2019;Casacuberta, Hickel & Kotsonis 2021) and experimental (e.g. Duncan et al 2014b;Eppink 2018Eppink , 2020bRius-Vidales & Kotsonis 2020Groot & Eppink 2021) studies revealed numerous unresolved aspects essential to the understanding of the FFS-CFI interaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNS are carried out with INCA, a conservative finite-volume-based flow solver (Hickel and Adams, 2008, Hickel et al, 2014, Casacuberta et al, 2020. The free-stream evolution and the DNS setup considered in this work are identical to the ones presented in a recent article (Casacuberta et al, 2021). The highly refined computational grid for the current DNS computations has 6760, 576, and 72 points along the chordwise, wall-normal, and spanwise directions, respectively, and more than 70 grid points cover the inflow boundary-layer thickness.…”
Section: A Steady Dnsmentioning
confidence: 99%